Current radiotracers to image neurodegenerative diseases - Solveig Tiepolt; Marianne Patt; Gayane Aghakhanyan; Philipp M. Meyer; Swen Hesse; Henryk Barthel; Osama Sabri (SpringerOpen, 2019)
Abstract The term of neurodegenerative diseases covers a heterogeneous group of disorders that are distinguished by progressive degeneration of the structure and function of the nervous system such as dementias, movement disorders, motor neuron disorders, as well as some prion disorders. In recent years, a paradigm shift started for the diagnosis of neurodegenerative diseases, for which successively clinical testing is supplemented by biomarker information. In research scenarios, it was even proposed recently to substitute the current syndromic by a biological definition of Alzheimer's diseases. PET examinations with various radiotracers play an important role in providing non-invasive biomarkers and co-morbidity information in neurodegeneration. Information on co-morbidity, e.g. Aβ plaques and Lewy-bodies or Aβ plaques in patients with aphasia or the absence of Aβ plaques in clinical AD patients are of interest to expand our knowledge about the pathogenesis of different phenotypically defined neurodegenerative diseases. Moreover, this information is also important in therapeutic trials targeting histopathological abnormalities. The aim of this review is to present an overview of the currently available radiotracers for imaging neurodegenerative diseases in research and in routine clinical settings. In this context, we also provide a short summary of the most frequent neurodegenerative diseases from a nuclear medicine point of view, their clinical and pathophysiological as well as nuclear imaging characteristics, and the resulting need for new radiotracers.